2014
DOI: 10.1103/physrevb.89.054302
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of the phonon dispersion and dielectric properties of wurtzite InP: Role of In4delectrons

Abstract: Although wurtzite InP nanowires have recently been grown, an accurate description of the wurtzite InP phonon dispersion is still missing. We calculate the ab initio phonon dispersion of wurtzite and zinc-blende InP using density-functional perturbation theory and a real space supercell approach. Our predicted optical phonon frequencies agree well with measured Raman data from InP nanowires. We find that treating In 4d electrons as valence electrons is required to accurately describe InP lattice dynamics and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…Moreover, it is also reasonable to expect a rather similar electronÀphonon interaction in WZ and ZB crystals due to their similar phonon dispersion curves. 55,56 This is consistent with preceding theoretical and experimental works highlighting the absence of a major role played by the crystal phase in determining some relevant thermal properties of NWs, such as specific heat, thermal energy group velocity, and phononÀphonon interactions. 55,57…”
Section: Articlesupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, it is also reasonable to expect a rather similar electronÀphonon interaction in WZ and ZB crystals due to their similar phonon dispersion curves. 55,56 This is consistent with preceding theoretical and experimental works highlighting the absence of a major role played by the crystal phase in determining some relevant thermal properties of NWs, such as specific heat, thermal energy group velocity, and phononÀphonon interactions. 55,57…”
Section: Articlesupporting
confidence: 89%
“…This is of relevance, for instance, in discriminating which structural characteristics of these nanostructures matter most in the reduced thermal conductivity usually exploited in NW-based thermoelectric devices. 55,57 …”
Section: Discussionmentioning
confidence: 98%
“…The inclusion of In 4d electrons in InP has already shown to improve the phonon and dielectric constant calculations [9]. [15,17] which depicts a reasonably well agreement between the present and available data.…”
Section: Methods Of Calculationsupporting
confidence: 82%
“…This is mainly due to the modified traditional electronic band structure, high electron mobility and small electron effective mass of InAs and thus providing new opportunities for the optoelectronics, photovoltaic and solar cell based semiconducting industry. At ambient conditions, bulk III-V semiconductor materials including InAs exhibit zinc blende (ZB) structure, however, in recent studies it has been shown that wurtzite (WZ) phase which is otherwise not possible in bulk form of III-V semiconductors can exist in the nanoparticles and nanowires (NW) [2,[6][7][8][9][10][11]. WZ phase has been shown to exist in the case of InAs nanowires [8,[10][11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation